ANALISIS ADMINISTRATIF DALAM SISTEM MERDEKA BELAJAR DI PROGRAM STUDI ADMINISTRASI PENDIDIKAN - Atani, Moudy Hadillah Atani; Idrus, Ali; Firman, Firman (Program Studi Adminsitrasi Pendidikan Universitas Jambi, 2021)
This study aims to determine the administrative merdeka belajar in the Education Administration study program. Descriptive qualitative was used in this study and samples were obtained from purposive sampling. Research instruments used in the form of observation, interviews, and documentation. Data analysis techniques using Miles and Hurben with data reduction, data presentation, and conclusion. The results showed that the functions of the administration in merdeka belajar in the Education Administration study Program were running well in accordance with the regulations issued by Permendikbud number 3 of 2020 concerning national standards for Higher Education. Related parties in the merdeka belajar program have several roles to support each other. Further research is needed to examine the administration of merdeka belajar more broadly.